2013
DOI: 10.1111/ger.12037
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a motivational–behavioural skills protocol for oral hygiene among patients with hyposalivation

Abstract: In patients with hyposalivation, the application of oral hygiene instruction based on cognitive principles and MI offers benefits for periodontal health. Longer-term studies are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 28 publications
(69 reference statements)
0
24
1
Order By: Relevance
“…The majority of studies investigated adults with a mean age of 50 years (n = 6), mostly subjects attending university programs or dental clinics. 1 , 6 , 14 , 22 , 40 The other four interventions were performed with parents of young children up to five years old in their communities, of immigrants, 15 indigenous 16 and low-income populations 13 , 18 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies investigated adults with a mean age of 50 years (n = 6), mostly subjects attending university programs or dental clinics. 1 , 6 , 14 , 22 , 40 The other four interventions were performed with parents of young children up to five years old in their communities, of immigrants, 15 indigenous 16 and low-income populations 13 , 18 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies used a trained counselor with extensive experience in MI, 1 , 6 , 13 , 18 two interventions were delivered by community members that received MI training, 15 , 16 one was performed by two dentists and another two studies did not report who delivered the intervention sessions. 19 , 22 Participants in most studies received individualized MI intervention, during dental visits or wellness child visits. 1 , 6 , 13 , 14 , 16 , 22 In one publication, it was not clear if the video sessions were performed in groups or individualized.…”
Section: Resultsmentioning
confidence: 99%
“…In a systematic review on the effectiveness of motivational interviewing for improving oral health, Cascaes et al [73] found conflicting evidence. Motivational interviewing improved tooth brushing in one study [118] but not in another [119]. It also improved fluoride application [120], but not interproximal tooth brushing [118] and dental utilization [121].…”
Section: Discussionmentioning
confidence: 99%
“…Motivational interviewing improved tooth brushing in one study [118] but not in another [119]. It also improved fluoride application [120], but not interproximal tooth brushing [118] and dental utilization [121]. While the dental caries improved in one study [120], motivational interviewing had no effect on this outcome in two other studies [119, 121].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation